Liberal world order and its critics civilisational states and cultural commonwealths - Pabst, Adrian (London Routledge, 2019)
This provocative book contends that the liberal world order is illiberal and undemocratic – intolerant about the cultural values of ordinary people in the West and elsewhere while concentrating power in the hands of unaccountable Western elites and Western-dominated institutions.
Introduction : liberal world order in retreat -- Hubris : the rise and fall of the liberal world order -- Backlash : the global revolt against liberalism -- Interregnum : the battle for hegemony -- Commonwealths : the case for cultural association -- Covenant : the resurgence of civilisation -- Conclusion : the once and future order.
"Routlege Focus"--Cover.
Includes bibliographical references and index.
Keywords: Cultural diplomacy; International organization; International relations; Liberalism